(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
This article discusses the importance and specific features of spiritual educational work in higher education institutions. In addition, the possibilities of modern information and communication technologies, which can be used in organizing spiritual educational work in higher educational institutions, are discussed